The silver yarn project : campaign to promote intergenerational bonding between youths and grandparents - Choong, Alan Jia Tang (2013)
This paper presents the communication campaign “The Silver Yarn Project”, a movement to promote intergenerational bonding between youths and their grandparents by four final-year students from the Wee Kim Wee School of Communication and Information, Nanyang Technological University.